DEVELOPING KUDA KEPANG ARTS IN A NEW LAND - Panuju, Redi; Widiarto, Didik Sugeng; Budiono, Agus Prasetya (Universitas Gadjah Mada, 2025)
This study aims to describe and analyze how Javanese migrants in the Kintap District conceptualize their creativity in developing the traditional art of Kuda Kepang. This art form originated in various regions of Java. Cultivating traditional arts in a new environment presents challenges due to differing socio-cultural contexts. It requires effort and self-concept to make changes and adapt to the new cultural environment. Additionally, there are challenges in navigating the performing arts ecosystem. This study employs an ethnographic methodology is a way to identify how meanings in cultural contexts are formed in social interactions. Data collection techniques used in-depth interviews and participant observation. The research reveals that past experiences serve as a source of inspiration for migrants to pursue the art of Kuda Kepang. These performances provide both personal catharsis and simultaneously entertain the community. The role of members of the regional People's Representative Council is very important in bridging the interests of Kuda Kepang art activists in Kintab with the South Kalimantan regional government, especially in accessing funds from the APBD (Regional Revenue and Expenditure Budget) for art performance activities and the procurement of other supporting facilities.